Analisis Tagline Merek yang Mengandung Unsur Pornografi di Media Sosial - Inda Nurdahniar (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Brands have economic value so protection is needed. Brand protection arises when registered. But this is excluded against brands that contain elements of decency. In reality many businesses use brands with the word, logo plus taglines that contain pornographic elements. The problem is seen if the brand continues to operate in the middle of society and even penetrated into social media. Based on the results of the study, the arrangement of brand taglines containing pornographic elements on social media is not specifically regulated but spread across various laws and regulations and there is overlapping. In fact the @ngocok.eskopi account with the trademark "Ngocok Es Kopi" passes as a registered trademark. Whereas when viewed with great disalness, both brands, logos and taglines used on social media have given implicit perceptions or images of pornography. In the era of digitization, social media is a potential media for means of promotion, it is fitting that there are special arrangements such as conventional promotion. Various regulations must also be integrated, such as the use of accounts on social media using legal identity (KTP), applying the tagline as a brand definition in the parent rule of the MIG Law, the passing of registered brands is the responsibility of regulators (human factors) and should not be charged to the system alone (technological factors), expanding the limitations of pornography to be explicit and implicit.